Correlation of the Caring Behaviour of Nurses With the Motivation of Patients Undergoing Haemodialysis - Pohan, Vivi Yosafianti; Yanto, Arief; Pranata, Satriya (Scripta Medica, 2024)
Background/Aim: There is a need to establish a satisfactory level of performance for nurses working in haemodialysis units, which will provide qualified competent nurses who will take care of patients. Thus, the purpose of this study was to analyse the caring behaviour of haemodialysis nurses with the motivation of patients undergoing haemodialysis. Methods: The research design was a descriptive correlation approach. The subjects of this study were patients who were undergoing therapy in the haemodialysis room. Researchers collected data for 1 month in September 2023. The relationship between nurses’ caring behaviour and haemodialysis patient motivation was determined by conducting a Spearman rank correlation analysis. Results: Out of 118 patients, 48.7 % of patients thought nurses had poor caring behaviour. The research results also showed that patient motivation in undergoing haemodialysis was in the low motivation category (47.8 %). There was a significant relationship between nurses’ caring behaviour and patient motivation in undergoing haemodialysis therapy (p = 0.0001). Based on the correlation coefficient value (r = 0.632), the two variables had a strong relationship. Conclusion: Nurses’ caring behaviour can increase patient motivation in undergoing haemodialysis therapy. Nurses’ caring behaviour still needs to be optimised because the interaction between nurses and patients in the treatment process provides support to patients.